Preparation of Methanyl Yellow Test Strip Based on Nata De Coco Membrane Immobilized Anthocyanin Extracted from Rosella Flower (Hibiscus Sabdariffa L.) - Lestari, Yunda; Widwiastuti, Hanandayu (LP2M IIK (Lembaga Penelitian dan Pengabdian Masyarakat Institut Ilmu Kesehatan) Bhakti Wiy, 2025)
Methanyl yellow is a synthetic dye used in the textile industry and its use is prohibited in food products. Its abuse is still found in crackers, noodles, tofu, and beverages. Methanyl yellow identification test used color reaction test, thin layer chromatography, paper chromatography, TLC scanner, and UV-Vis spectrophotometry. So, in this study, the methanyl yellow test strip test method was developed using anthocyanin immobilized nata de coco membrane with rosella flower extract. The purpose of this study was to determine the selectivity and sensitivity of the resulting test strips. The test strip consisted of nata de coco membrane and rosella flower extract reagent. The test strip made has an optimum contact time of 10 seconds. In the analysis using FTIR, the functional groups O–H, C–H alkanes, C=O, C=C alkenes, C–O, and C–H alkenes on the test strip indicated anthocyanin compounds. In the test strip which was reacted with methanyl yellow the functional group identified had a weaker absorption than the test strip which had not been reacted. The characterization test includes a detection limit test with detection capability starting at a concentration of 6 ppm and lifetime test results, up to the 21st day the strip test can be used, storage using dark bottles is better than clear bottles. So that the resulting test strips provide good data and can be used for quick measurements.